A case study on the production effectiveness of the sewing system of Blue Bell Comodities, Incorporated - Reyes, Ronalda Tena
The study was conduced in the BLUE BELL COMMODITIES, INC., a typical garment manufacturing company, to determine the aforementioned company's capability of meeting the demands of their buyers using a certain type of sewing system. This will help the company assess their sewing system; to find out what aspects of the system needs improvement. Through a case study method conducted in the company's sewing department which used observations, interviews, and examinations of existing records, the researcher was able to know the present buyers of the company and their demands with regard to the products they have ordered, the type and process of sewing system they are using, and the strong and weak points of the system. The study found out that their buyers demand high quality garments produced in shorter lead time and a a lower cost. With the use of the Multiple Flow Operation Bundle System, the company is capable of meeting effectively the demand of buyers on quality. Thus, it can be considered as the strong point of the system. On the other hand, the inability of the system to meet the buyers' demands for shorter lead time and lower garment cost are considered to be the weak points of the company's sewing system. This indicates that the aspects of the system that hinder the company in meeting requirements, which include sequence of process and clerical and handling operations, should be improved.